The Intersection of Policy, Economics, and Workforce Resilience in Global Healthcare Systems: A Narrative Review - Novianita Rulandari; Multy Syaddam Nirwan; Putri Ayu Lestari (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: In this study, we aimed to examine systemic barriers and facilitators affecting healthcare workers, including policy frameworks, economic conditions, and organizational structures. With healthcare worker support mechanisms playing a critical role in ensuring the effectiveness and sustainability of healthcare systems, our objective was to assess the impact of these factors on healthcare worker well-being, service quality, and healthcare disparities, particularly among marginalized populations. Methods: This comprehensive narrative review involved an in-depth analysis of peer-reviewed literature from major academic databases. The study focused on healthcare worker experiences, policy impacts, and cultural considerations. Articles were selected based on relevance to healthcare worker support mechanisms, and data synthesis was conducted to identify key themes. Results: The primary outcome of the study indicated that inadequate healthcare worker support contributes to disparities in care, burnout, and reduced service quality. Additionally, findings emphasized the importance of policies promoting equitable resource allocation, mental health support, and interdisciplinary collaboration. Economic stability and culturally sensitive healthcare models were identified as crucial for improving worker well-being and patient outcomes. Conclusion: In conclusion, our study contributes to the understanding of healthcare worker support by highlighting the systemic barriers and facilitators affecting their well-being and performance. This research provides insights into the need for policy reforms and organizational interventions to enhance healthcare workforce resilience. Future studies should focus on longitudinal evaluations of healthcare worker support mechanisms and comparative analyses of different healthcare systems, ultimately advancing strategies for sustainable and effective global healthcare systems.